2002
DOI: 10.1097/00001756-200208070-00016
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of temporal attention in patients with schizophrenia

Abstract: Evidence is accumulating that attention impairment is a core cognitive deficit in patients with schizophrenia. Here we investigate whether they are impaired in the temporal deployment of attention. Specifically, we explore how allocation of processing resources at one time point might affect the processing of a subsequent event differently in normal and schizophrenia subjects. Thirty patients and 31 age- and education-matched control subjects participated in a rapid serial visual presentation task, in which tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 10 publications
1
31
0
1
Order By: Relevance
“…More specifically, diminished GABA levels are thought to reduce evoked gamma oscillations and in turn, to minimize neural synchrony, resulting in abnormally frequent integration of sensory input (Paine, Slipp & Carlezon Jr, 2011). Coincidentally, schizophrenia patients also tend to have increased AB magnitude (Li et al, 2002). Although only correlational in nature, these studies underline the possible impact of GABA concentrations on (visual) integration processes.…”
Section: Discussionmentioning
confidence: 86%
“…More specifically, diminished GABA levels are thought to reduce evoked gamma oscillations and in turn, to minimize neural synchrony, resulting in abnormally frequent integration of sensory input (Paine, Slipp & Carlezon Jr, 2011). Coincidentally, schizophrenia patients also tend to have increased AB magnitude (Li et al, 2002). Although only correlational in nature, these studies underline the possible impact of GABA concentrations on (visual) integration processes.…”
Section: Discussionmentioning
confidence: 86%
“…In the clinical population, an increase of AB has been demonstrated in patients with schizophrenia (Cheung et al 2002;Li et al 2002), Specific Language Impairment (Lum et al 2007), depression (Rokke et al 2002) and attention deficit/hyperactivity disorder (ADHD; Armstrong and Munoz 2003;Carr et al 2006;Hollingsworth et al 2001;Li et al 2004;Mason et al 2005;Ray Li et al 2005). Lesions studies have demonstrated that abnormal AB can occur with different chronic focal brain lesions in a network of structures involved in vision and/or attention (Rizzo et al 2001) such as the frontal (Husain et al 1997;Richer and Lepage 1996) and the parietal (Shapiro et al 2002) cortices as well as the cerebellum (Raymond et al 1992;Schweizer et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with spatial neglect (Masud et al, 1997), schizophrenia (Li et al, 2002), attention deficit hyperactivity disorder (Hollingsworth et al, 2001), Parkinson's disease (Vardy et al, 2003) and prefrontal lesions (Rizzo et al, 2001) all demonstrate AB deficits. Such findings suggest that the AB task may be useful in understanding underlying attentional deficits associated with these disorders.…”
mentioning
confidence: 99%